A educomunicação e a divulgação científica sobre transgenia - Alves, Selmar Becker (2018)
This study starts by the hipothesis that each information, when the diversity of ideas and its intentions is considered, becomes knowledge. So, we question that if journalism as a form of knowledge, is capable of developing knowledge about, or knowledge of, or other form of knowledge. We also question if journalism as a form of knowledge allows people to analyse very critically the facts, make its own opinions and get new knowlwdge. In this sense, it had the objective of developing a comunication tool based on the Ecological Ecosystem. We are showing Educomunication as a strategy that promotes at the same time the dialoge and the distancing from the information showed so it can create new knowledge. As an example, the transgenics theme tried to promove the observation, quantification, description and giving a meaning for the information about it gaved by the agentes that regulate its exibition and application in Brazil. Based on problem s ituations, this study intends to explore the legitimacy of the studies about transgenics on media (editorials, news articles, reports, cover letters and books) by everyone envolved. Based on the contente analysis technique, we made indicators (Precaution Speech, Confirmation Speech, Provocation Speech), using Educomunication as a beacon of scientific divulgation on media. Using Brecht’s cannons (1978), the Communicative Ecosystem tool has accepted the diverse knowledge on the studied texts and has approached Science and Society.